Is The Microlearning Approach A New Way to Influence Learners’ Attitudes Towards Nursing Bioscience Education? (International Journal of Nursing Education, 2026)
Objective: Historically, nursing students have found bioscience subjects challenging and anxiety provoking. To alleviatethese factors, an online industry-based short course, Biochemical Basis for Human Life (BBHL) was developed. A surveywith narrative analysis was used to explore learners’ experience and satisfaction with the course and evaluate theeffectiveness of microlearning approach in delivering nursing bioscience education.Methods: Learners enrolled in the short course and following the course completion, they were invited to submit theEnd of Course Feedback survey. The survey included quantitative measures of course satisfaction, demographicspertaining to learners’ country of origin and two open ended qualitative questions.Results: A total of 444 learners were enrolled in the course, with 33.3% completion rate (148/444). Out of the learnerswho completed the course, 89.9% (133/148) completed the End of Course Feedback survey. Across all questions,agreement rates exceeded 90%, with negligible disagreement or nonresponse in relation to course satisfaction. Out of thelearners who provided a qualitative response, majority expressed positive attitudes towards course delivery and courseimpact.Conclusions: This study highlighted the beneficial nature of the course and its microlearning approach in relationto nursing bioscience education. Furthermore, this study provides a new strategy for educators where a bite-sizedlearning can be used as pre-classroom preparation for students to enhance student engagement and decrease burdenassociated with extensive material coverage in the classroom.
Keywords: Bioscience education; Microlearning; Nursing; Teaching models; Workforce development.